Failure locator - Dwojak, Adam (Instal, 2021)
It is the duty of the operator of a district heating network, also a pre-insulated one, to carry out regular inspections and, if the situation requires, to make repairs. The location of the excavation for the repair must be indicated with sufficient precision, which reduces the cost of the entire operation. In the case of pre-insulated pipelines, sometimes stationary devices called failure locators are used. The author considers the validity of their use.